In the footsteps of Crazy Horse - Marshall, Joseph, 1945- (Amulet Books, 2015)
Teased for his fair coloring, eleven-year-old Jimmy McClean travels with his maternal grandfather, Nyles High Eagle, to learn about his Lakota heritage while visiting places significant in the life of Crazy Horse, the nineteenth-century Lakota leader and warrior, in a tale that weaves the past with the present. Includes historical note and glossary.